Nemzeti kisebbség és autonómia kérdés a Kárpát-medencében - Szilágyi, István (Közép-Európai Közlemények, 2013)
The 21st century is the age of globalisation, the era of connections between cultures and civilisations representing different values and value systems. Our century is also the time of minorities, the time of identities moving back towards nationality-consciousness, the time of minority rights and autonomies and the time of integrational, disintegrational, territorisational, deterritorisational and reterritorisational tendencies in addition to the implementation of the principle of subsidiarity. All these factors have a significant influence on the multinational state structures in both the developed and semi-peripheral areas of the world. The breakup of the Soviet Union, Yugoslavia and Czechoslovakia, the federal and structural transformations in Great Britain, Spain and Italy and the state failures in the Third World are manifestations of the same phenomenon. The transformation of the unitarian centralised states and territorial systems carried out by devolutional, decentralised and region-regulatory processes as well as the development of the local councils and self-governing systems representing territorial, personal and national autonomies of different levels indicate general tendencies. In the life of national minorities living in the territories of multinational states the mother tongueis the primary representative of national identity: it expresses a strong sense of belonging to the given national community. Along with the legal frame-work that serves to secure minority language rights and institutional guarantees given to various types of minority representation, this serves as an increasingly powerful factor in the lives of national minorities. On the basis of the National Censuses in 2011, the study analyses the possible framework, circumstances and the demographic factors in the Carpathian Basin.